What The VCs Say - Sunday Star, (2008)
UN1VERSITI Malaya s improved position shows that the strategic plan which was implemented two years ago under the leadership of our Vice chancellor Datuk Rafiah Salim and the excellent support and teamwork of our staff is bearing fruit Our focus in implementing the strategic plan is to ensure the international competitiveness of UM in recognition of the fact that we are now living in a borderless global community.